Influence Ofexercise High Hurdle Jump and Forward and Lateral Hurdle Jump on Increasing Leadstrength and Power Muscle - Mochamad Ilham Agung Prilaksono; Oce Wiriawan; Fransisca Januarumi Marhaendra Wijaya (BIRCU, 2021)
Treat sports players using a new type of exercise or a method that has been popular in the world of increasing physical abilities in recent years, namely the varied plyometric method so that athletes don't feel bored. Types of plyometric exercises high hurdle jump and forward and lateral hurdle jump are two types of plyometric exercises but their implementation is different. Therefore, it is necessary to provide learning resources and human resources who are able to provide material for plyometric training methods. This study aims to determine the effect of high hurdle jump and forward and lateral hurdle jump exercises on increasing leg muscle strength and power. This research uses a quantitative approach to the type of classroom action research. The research method uses experimental methods. The research design used the none equivalent (pretest and post-test) control group design. The independent variables in this study are high hurdle jump training, forward and lateral hurdle jump exercises, and the dependent variable is leg muscle strength and power. The sample in this study amounted to 30 students of class X who used the random sampling technique. Analysis of the data used in this study to test the effect is paired t-test. Furthermore, to test the difference in effect between the treatment and control groups was carried out using one way ANOVA on the normal data distribution. The test results showed that there was a significant difference in the high hurdle jump experimental group on the variable leg muscle strength and power with a significance value of p 0.00 <0.05, a percentage increase of 6.79% in the strength variable and 6.22% in the leg muscle power variable. There is a significant difference in the forward and lateral hurdle jump experimental group on the variable leg muscle strength and power with a significance value of p of 0.00 <0.05, a percentage increase of 6.04% in the strength variable and 7.51% in the leg muscle power variable. High hurdle jump exercises are more effective than forward and lateral hurdle jumps to increase strength and forward and lateral hurdle jumps are more effective than high hurdle jumps to increase leg muscle power.